Stop Burying the Lede: The Essential Role of Indigenous Law(s) in Creating Rights of Nature. Issue 3 (2nd November 2020) - O'Donnell, Erin; Poelina, Anne; Pelizzon, Alessandro; Clark, Cristy
Abstract: The rapid emergence of rights of Nature over the past decade across multiple contexts has fostered increasing awareness, recognition, and, ultimately, acceptance of rights of Nature by the global community. Yet, too often, both scholarly publications and news articles bury the lede – namely, that the most transformative cases of rights of Nature have been consistently influenced and often actually led by Indigenous peoples. In this article we explore the ontologies of rights of Nature and earth jurisprudence, and the intersections of these movements with the leadership of Indigenous peoples in claiming and giving effect to their own rights (while acknowledging that not all Indigenous peoples support rights of Nature). Based on early observations, we discern an emerging trend of increased efficacy, longevity, and transformative potential being linked to a strongly pluralist approach of lawmaking and environmental management. A truly transformative and pluralist ecological jurisprudence can be achieved only by enabling, and empowering, Indigenous leadership.